Evaluation of the male reproductive toxicity of the anthocyanin-rich standardized extract of hibiscus sabdariffa L.loaded niosomes in sprague dawley rats - Ghazali, Mohamad Luqman Hanafi (2021)
Hibiscus sabdariffa has long been widely utilised for medicinal purposes. Aqueous extract of H. sabdariffa encapsulated in niosome (AEHS-Nio) was formulated to improve the effectiveness of this plant extract. It was administered to forty male Sprague Dawley rats at four different dosages 0 (control), 250, 500, and 1000 mg/kg/day by oral gavage for 63 days to evaluate the potential effects of AESHNio on the male reproductive system. A substantial number of parameters were evaluated throughout the treatment period that was comprised of three phases; premating, mating, and post-mating. Results obtained demonstrated that the effects of AEHS-Nio on the male rat reproductive system were slightly significant for certain doses. No mortality and any signs of physical toxicity were observed. The mating performance was also not affected. However, due to the established anti-obesity effects of H. sabdariffa extract, the bodyweight of rats were considerably changed. As a consequence, the reproductive organ weights were found to be statistically different. Furthermore, AEHS-Nio increased the testosterone levels and sperm counts of the 250 and 1000 mg/kg dose groups, while the 500 mg/kg dose group showed considerably low levels for both parameters. The 500 mg/kg dose group was detected to exhibit inconsistent data for certain parameters when compared to other groups, which might be caused by confounding factors instead of AEHS-Nio. Therefore, the current data suggest that AEHS-Nio did not toxic to the reproductive system of male rats. Nevertheless, AEHS-Nio should be consumed with caution as long as the dose administered does not exceed 250 mg/kg of bodyweight a day.The human risk on male reproductive parameters associated with its use should also be reasonably estimated.